Does the China–Pakistan free trade agreement benefit the vegetable exports of Pakistan? A gravity estimation - Khan, Humayun; Chen, Yangfen; Lv, Liu (Frontiers in Sustainable Food Systems, 2024)
In the backdrop of criticism that the China-Pakistan Free Trade Agreement has disproportionately favored China, particularly in agricultural trade, there has been a surge in Pakistan’s imports, leading to a trade deficit. This study attempts to evaluate the impact of CPFTA 1&2 on the vegetable exports of Pakistan which is an important sector of the agricultural industry. A panel data set of Pakistan’s vegetable exports to its trading partners from 2003 to 2021 was analyzed with the extensively used gravity model of trade. The vegetable export data was sourced from the International Trade Centre (ITC) which is based on the Pakistan Bureau of Statistics. The results suggest that the China-Pakistan Free Trade Agreement (CPFTA-I) has a positive association with Pakistan’s vegetable exports to China. However, trade liberalization with Afghanistan, Sri Lanka, and Malaysia plays a more substantial role in driving Pakistan’s vegetable exports. CPFTA-II has not had a measurable or statistically significant impact on the vegetable exports of Pakistan as this period was highly influenced by COVID-19. The results of colonialism variables show that Pakistan is exporting more to countries with the same colonial history. Moreover, the results of the geographical variable suggest that Pakistan should explore more close markets to expand vegetable exports. Policy implications suggest the need to reduce trade costs, leverage CPEC infrastructure, enrich trade relations with neighboring countries, and involve business professionals in policy negotiations.